Pengaruh Resin Epoksi Terhadap Mortar Polimer Ditinjau dari Kuat Tekan, Kuat Tarik Belah, Daya Serap Air dan Scanning Electron Microscope - Arif, Joksan; Husni, Hasti Riakara; Sebayang, Surya (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
Polymer mortar is a material formed through the process of building a composite concrete andbuilding polymers. Polymer mortar development efforts have been conducted in developedcountries. Until now the development of polymer mortar is still underway to reduce the use of thesemen, in order to anticipate the global warming. One of them is by using a polymer adhesivecement replacement material so produced a powerful mortal in a shorter time.On research was created mortal polymers without cement, fine aggregate and epoxy resin as thebinder of concrete. The composition of the raw materials of polymer mortar made with acomparison between aggregate and epoxy resins, with her blend of 20%, 25% .30%, 35%, 40% (%of the total weight of the aggregate). Mortar has been mold then dried in an oven at a temperatureof 600 C for 24 hours. Parameters measured include: water absorption, compressian strength,tensile strength, and microstructure analysis using a Scanning Electron Microscope (SEM). Theobservations suggest that the optimum condition of polymer mortar obtained on composition: 65%of the aggregate (aggregate) and 35% epoxy resin (% of weight of fine aggregate). In this state ofpolymer mortar characteristics obtained as follows: water absorption = 3,57%, compressianstrength = 6.80 MPa, and tensile strength = 1.75 Mpa. The microstructure of the polymer concreteanalyzed using SEM. Result showed that pore size distribution was uneven, and wisps of epoxyresin ≤ 30 μm.Keywords: compressian strength, tensile strength, water absorption, Scanning ElectronMicroscopy (SEM), polymer mortal.